Efek Perendaman Benih Dengan Berbagai Media Tanam Pada Pertumbuhan Bibit Sengon - Suud, Mochammad; Zuhroh, Mimik Umi; Kulsum, Ummi (Agrotechbiz : Jurnal Ilmiah Pertanian, 2024)
Sengon plants today are often found in rural areas. With a fairly short harvest period, but the harvest is quite a lot. Often processed into raw materials for furniture and other home needs. This research was tried in the 4th to 7th month of 2022 located in Krajan Village, Dringu District, Probolinggo Regency. This study chose RAK as the method. The factors used are two, namely the 1st factor (4 levels) and the 2nd factor (3 levels). This studies intends to: 1) Recognize the consequences of the type of seed irrigation device on the development of sengon seeds. 2) Recognize the consequences of sowing media arrangement on the development of sengon seeds. 3) Recognize the relationship between the consequences the kind of seed irrigation media & the arrangement of sowing media in the growth of sengon seeds.